On the relativity of old and new media: A lifeworld perspective. (August 2019) - Menke, Manuel; Schwarzenegger, Christian
It is an old, yet, accurate observation that the 'newness' of media is and most probably will continue to be a catalyst for research in media and communication studies. At the same time, there are numerous academic voices who stress that studying media change demands an awareness of the complexities at play interweaving the new with the old and the changes with the continuities. Over the last decades, compelling theoretical approaches and conceptualizations were introduced that aimed at grasping what defines old and new media under the conditions of complex, disruptive media change. Drawing from this theoretical work, we propose an empirical approach that departs from the perception of media users and how they make sense of media in their everyday affairs. The article argues that an inquiry of media change has to ground the construction of media as old or new in the context of lifeworlds in which media deeply affect users on a daily basis from early on. The concept of media ideology (Gershon, 2010a, 2010b) is used to investigate notions of 'oldness' and 'newness' people develop when they renegotiate the meaning of media for themselves or collectively with others. Based on empirical data from 35 in-depth interviews, distinct ways how the relativity but also relationality of old and new media are shaped against each other are identified. In the analysis, the article focuses on the aspects of rhetoric, everyday experiences, and emotions as well as on media generations, all of which inform media ideologies and thereby influence how media users define old and new media.